Stem cell plasticity, acetylation of H3K14, and de novo gene activation rely on KAT7 - Andrew J. Kueh; Maria I. Bergamasco; Anna Quaglieri; Belinda Phipson; Connie S.N. Li-Wai-Suen; Ingrid M. Lönnstedt; Yifang Hu; Zhi-Ping Feng; Chris Woodruff; Rose E. May; Stephen Wilcox; Alexandra L. Garnham; et al. (Cell Reports, 2023)
Summary: In the conventional model of transcriptional activation, transcription factors bind to response elements and recruit co-factors, including histone acetyltransferases. Contrary to this model, we show that the histone acetyltransferase KAT7 (HBO1/MYST2) is required genome wide for histone H3 lysine 14 acetylation (H3K14ac). Examining neural stem cells, we find that KAT7 and H3K14ac are present not only at transcribed genes but also at inactive genes, intergenic regions, and in heterochromatin. KAT7 and H3K14ac were not required for the continued transcription of genes that were actively transcribed at the time of loss of KAT7 but indispensable for the activation of repressed genes. The absence of KAT7 abrogates neural stem cell plasticity, diverse differentiation pathways, and cerebral cortex development. Re-expression of KAT7 restored stem cell developmental potential. Overexpression of KAT7 enhanced neuron and oligodendrocyte differentiation. Our data suggest that KAT7 prepares chromatin for transcriptional activation and is a prerequisite for gene activation.